2016
DOI: 10.1186/s12913-016-1861-0
|View full text |Cite
|
Sign up to set email alerts
|

What is the role of community capabilities for maternal health? An exploration of community capabilities as determinants to institutional deliveries in Bangladesh, India, and Uganda

Abstract: BackgroundWhile community capabilities are recognized as important factors in developing resilient health systems and communities, appropriate metrics for these have not yet been developed. Furthermore, the role of community capabilities on access to maternal health services has been underexplored. In this paper, we summarize the development of a community capability score based on the Future Health System (FHS) project’s experience in Bangladesh, India, and Uganda, and, examine the role of community capabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
4
0
1
Order By: Relevance
“…Studies in Afghanistan, Democratic Republic of Congo and Malawi found that CSCs have facilitated in increasing community participation and awareness, accountability of providers and utilisation of services [ 15 , 16 , 22 ]. The findings in this paper, that active community participation has a positive effect on improving community awareness and provider accountability and thus enhance utilisation of health services are also consistent with other studies [ 11 , 12 ] in the study area. Findings from the study regarding service utilisation rate in intervention and control CCs at baseline are consistent with findings from a study on assessment of CCs supported by the World Health Organisation [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Studies in Afghanistan, Democratic Republic of Congo and Malawi found that CSCs have facilitated in increasing community participation and awareness, accountability of providers and utilisation of services [ 15 , 16 , 22 ]. The findings in this paper, that active community participation has a positive effect on improving community awareness and provider accountability and thus enhance utilisation of health services are also consistent with other studies [ 11 , 12 ] in the study area. Findings from the study regarding service utilisation rate in intervention and control CCs at baseline are consistent with findings from a study on assessment of CCs supported by the World Health Organisation [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…Community engagement in the management of healthcare delivery and local level planning has been seen as a successful strategy to improve health service delivery and increase utilisation [ 10 , 11 ]. Strong cohesion of community and social network have also helped to improve healthcare delivery and utilisation of health services in similar settings [ 12 , 13 ]. Social accountability approaches such as citizen report cards, village health committees and community score cards (CSC) have helped in increasing accountability in health facility monitoring [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The way women and their families perceive the benefit and/or the need for an institutional delivery with skilled attendance influences their decision-making process to seek skilled care for either a routine delivery or a complication during delivery. This perception is in turn influenced by their general awareness of the risks of labor and delivery and their capabilities, in terms of material resources, to access health care [7]. The strong correlation between health institution delivery and mother's education and wealth quintile has also been well documented in the literature on Sub-Saharan Africa [8].…”
Section: Introductionmentioning
confidence: 95%
“…A sample size of 383 was calculated for a 95% confidence level, using OpenEpi version 3 for sample size calculation for the proportion of women who deliver in the facilities assuming a hypothesized facility delivery rate for South Sudan of 21% [7] and design effect (for cluster surveys) of 1.5, and allowing 10% for missing data.…”
Section: Study Population and Samplingmentioning
confidence: 99%
“…Furthermore, we study social capital as an asset that a slum community can employ to encourage higher resilience, i.e., to maintain their current location. Social capital in this study is seen as a form of collective community capability, which is defined as an asset that is available to a community for achieving their goals [66]. The extent to which a community can mitigate a risk is based on its capability [44].…”
Section: Conceptual Frameworkmentioning
confidence: 99%